INTEGRATION OF ARTIFICIAL INTELLIGENCE INTO EDUCATIONAL PLATFORMS FOR EFFECTIVE LANGUAGE LEARNING - Gulyamova, Gulnora; Rasulmuhamedova , Durdona (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The use of artificial intelligence (AI) technologies in language teaching is one of the most promising and dynamically developing areas at the intersection of computer science, linguistics, and pedagogy. Purpose. The study aimed to identify key factors and prospects for the use of AI technologies in the field of language education in Uzbekistan, addressing the unique linguistic and cultural characteristics of the country. Methods. The study analysed existing approaches to integrating AI into language teaching, explored the technical and pedagogical aspects of introducing artificial intelligence technologies into educational platforms in Uzbekistan, and assessed the potential for extending this experience to language education in the country. Results. The study results demonstrate that Uzbekistan has a sufficiently developed technological infrastructure for implementing artificial intelligence projects in education. Conclusions. Research findings also highlighted artificial intelligence's valuable potential for advancing multilingual education initiatives, simultaneously supporting the teaching of Uzbek as the official language while preserving and developing minority languages. The results of the study can be used to create a comprehensive strategy for introducing artificial intelligence into the educational system of Uzbekistan.